Idiopathic Intracranial Hypertension (IIH) After Spinal Surgery Due to Spondylitis Tuberculosis - Akhyar Nur Uhud; Hamzah; Anang Maulana Yusuf (Faculty of Medicine-Universitas Airlangga, 2026)
Introduction: Idiopathic intracranial hypertension (IIH) is a rare syndrome with an unclear etiology but causes clinically increased intracranial pressure (ICP). This disorder is diagnosed by ruling out the possibility of a diagnosis that can cause intracranial hypertension. Idiopathic intracranial hypertension that appears after spinal surgery is one of the rare occurrences. Objective: This report describes a rare presentation of postoperative idiopathic intracranial hypertension with Cushing’s reflex and highlights the clinical utility of noninvasive intracranial pressure monitoring using transcranial Doppler and optic nerve sheath diameter measurement. Case Report: We present a case of a 21-year-old woman with tuberculous spondylitis who underwent spinal surgery. After surgery, the patient showed signs of intracranial hypertension with Cushing reflex. Then, the patient was managed with intracranial control with adequate sedation and analgesia and monitored using transcranial Doppler (TCD) and optical nerve sheath diameter (ONSD). Dexamethasone and acetazolamide were also administered to the patient to lower ICP. The patient was then released from the hospital without any complications or morbidities. Discussion: Idiopathic intracranial hypertension after spinal surgery is a rare condition with high morbidity due to high ICP. Appropriate and prompt treatment could reduce morbidity, and ICP could be monitored using TCD and ONSD. Conclusion: Idiopathic intracranial hypertension is a rare syndrome with high morbidity due to increased ICP. The key to managing IIH is to decrease ICP and avoid morbidity due to high ICP through close monitoring of ICP. Early recognition combined with noninvasive ICP monitoring may help guide timely management and prevent neurological morbidity.